Cytotoxic effect of 2, 5-dimethyl-celecoxib as a structural analog of celecoxib on human colorectal cancer (HT-29) cell line - Nikanfar, Saba; Atari-hajipirloo, Somayeh; Kheradmand, Fatemeh; Rashedi, Jalil; Heydari, Amir (Cellular and Molecular Biology, 2018)
Dimethyl-celecoxib (DMC), a close derivative of celecoxib (CXB) with a low COX-2 inhibitory function, exhibits signiï¬cant anti-neoplastic properties. In this study, we have investigated the effect of CXB and DMC on the human HT-29 cell line. The cellular viability, caspase-3 activity, and VEGF, NF-ÎºB, and COX-2 genes expressions were assessed respectively with MTT, colorimetric, and real-time RT-PCR methods. DMC, a close analogue of CXB, was more potent in inhibiting the growth of cells (IC50: 23.45 µM at 24 hr) than CXB (IC50: 30.41 µM at 24 hr). Both CXB and DMC caused a significant difference in caspase-3 activity compared to the control group. DMC significantly decreased the NF-ÎºB expression. Down-regulation of the COX-2 mRNA expression in the celecoxib-treated group was significant compared with that in the DMC-treated group. Alterations in the mRNA expression of VEGF were not significant between the groups. Owing to the more potent growth inhibitory effects of DMC compared to that of celecoxib, it may be important to conduct research on the anticancer application of this compound, which can reduce the side effects relating to COX2 inhibition.